Distribusi Zakat Fitrah Secara Merata Dalam Pespektif Sosiologis: Studi di Masjid Baitussalam Belangan Temanggung - Abdul Munjid , Mohammad; Jamiudin, Jamiudin; Ulfa , Hidayatun (El-Qenon: Journal of Islamic Law, 2024)
The distribution of zakat is carried out in accordance with the provisions of Allah as stated in the holy book of the Qur’an and the Sunnah of the Prophet. These provisions become the applicable law in Islam. However, there are certain communities that do not adhere to Allah’s provisions in their practice of zakat fitrah. This is a legal phenomenon that occurs within society, especially in the Islamic community. The practice of distributing zakat fitrah at Masjid Baitussalam in the Belangan Hamlet is done uniformly to the entire community without distinguishing the mustahiq (recipients of zakat). This, of course, presents a problem. The research problem in this study is as follows: (1) How is the practice of distributing zakat fitrah conducted at Masjid Baitussalam in the Belangan Hamlet? (2) What is the sociological analysis of the practice of distributing zakat fitrah at Masjid Baitussalam in the Belangan? This research is a field study using a Historical-Sociological and qualitative method. The data collection techniques used are interviews and observations. After the data is collected, it is analyzed using an inductive method with a sociological approach. From this research, it can be concluded that: (1) The equal distribution of zakat fitrah at Masjid Baitussalam in the Belangan Hamlet, while not permissible in principle, is done by the community due to social jealousy factors and to ensure that zakat is distributed quickly. (2) The use of zakat leftovers at Masjid Baitussalam in the Belangan Hamlet Village is not permissible in Islamic law because often those who receive it are not eligible zakat recipients. However, because it has been done traditionally by the community for generations, it has become a cultural factor. The committee distributes the zakat leftovers with the intention of quickly depleting the remaining zakat.